FUNDAMENTAL WATER CONSUMPTION PER CAPITA IN VARAMIN - A.H. Mahvi; H. Khorsandi (Tehran University of Medical Sciences, 1999)
One of the most important parameters essential in different water supplies, treatment, transfer and distribution projects, is water consumption per capita. But unfortunately in many cases, statistics and date available in texts or irrelevant samplings are used. Varamin is a region located in South east of Tehran. Among the most important problems in this region, insufficiency of personnel prolonged reading and registration of counter readings, illegal use of water may be mentioned. In order to determine accurately the panel of water consumption per capita per day, this research was done in all four seasons in 1995 (especially in hot days). After gathering basic data, they were analyzed by SPSS software reaching a value of 240.76 4.968LPCD with %95 accuracy for total water consumption, with maximum daily and hourly factors of 1.47 0.047 and 1.578, respectively. Average domestically consumption per capita (LPSD) 208.37 2.037; Average industrial and commercial per capita (LPSD) 2.5 0.86; Average general uses per capita (LPSD) 1.39 0.57; General Parks per capita (LPCD) 4.99; and Water loss per capita (LPSD) 22.61 1.501. It should be mentioned that the standards for domestic water was 75-150 LPCD, 10-45 LPCD for industrial uses and 10-20 LPCD for general uses. Simultaneously, designing a computerized system management which, using FoxPro software, a file was designed which was well coordinated with water price system in water and W.W company which using its data, the mean daily water consumption based on different types of connections and pipe diameter, this program, may be regarded as one of the most accurate recommended systems in determining LCPD in other regions of the country.